MENGGALI MAKNA HADITS TENTANG ANJURAN BERSIWAK SEBELUM SHOLAT: PERSPEKTIF FIQH DAN KESEHATAN - Arif Fikri; Rizki Melinda Siregar; Hamzah Taha Aziz (Yayasan Baitul Hikmah al-Zain, 2025)
This research aims to analyze hadiths relating to the recommendation to perform siwak before praying, with the aim of understanding the legal basis and benefits of this practice in the context of worship. The methodology used in this research is a literature study, by analyzing various relevant hadith sources as well as the interpretations of scholars regarding the importance of siwak before prayer. The results of the research show that doing siwak before prayer has a strong basis in the hadith, where Rasulullah SAW encouraged his people to do siwak as physical and spiritual preparation before carrying out the prayer service. Apart from that, siwak also has health benefits, such as cleaning teeth and mouth, and increasing devotion in worship. This research also reveals that there is agreement among the ulama regarding the importance of siwak as part of a perfect prayer procedure.